(untitled) (World Bulletin of Social Sciences, 2021)
In peach orchards, the spread of diseases caused by Taphrina deformans, Slasterosporium sarpophilum, Monilinia fructigena, Sphaerothesa rannosa and other fungi causes great damage to crops. In recent years, infestation with Monilinia fructigena among these fungi has increased significantly. Hence the development and damage of this fungus were studied.